Steam Assisted Waste Oil Stove Produces High Velocity Flow: Kompor Minyak Limbah Bertenaga Uap Menghasilkan Aliran Berkecepatan Tinggi - Fernanda, Ardhi Shefta; Mulyadi; Widodo, Edi; Akbar, Ali (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Waste management and alternative energy utilization are critical challenges in sustainable engineering systems. Specific Background: Conventional combustion systems often rely on mechanical devices such as blowers to improve combustion, which increases complexity and energy consumption. Knowledge Gap: Limited studies integrate steam boiler systems directly into combustion processes to generate airflow without additional mechanical assistance. Aims: This study aims to design and analyze a steam-assisted combustion stove using waste oil as fuel, focusing on thermal performance, steam generation, and flow characteristics. Results: The system employs a steam boiler with dimensions of 40 × 40 × 40 cm, producing steam at a rate of 0.0170 kg/s with a required heating power of 38,382 W and fuel consumption of 1.2 kg/h. Simulation results show flow velocities ranging from 52.8 m/s in the pipe to 531 m/s at the nozzle, indicating significant acceleration due to geometric constriction. Novelty: The integration of a steam boiler into a combustion system enables the conversion of thermal energy into kinetic energy flow without mechanical air supply devices. Implications: The design provides a practical solution for improving combustion performance using waste-derived fuel while maintaining system simplicity and safety. Keywords: Steam Boiler, Waste Oil Fuel, Combustion System, Flow Velocity, Thermal Design Key Findings Highlights Steam generation reached stable mass flow under defined thermal conditions Nozzle configuration created substantial acceleration in fluid stream Structural design met pressure resistance and operational safety criteria